Comparing Responses of Ursolic Acid in Murine Macrophages Infected with Mycobacterium smegmatis and Mycobacterium avium - Pitaloka, Dian; Jihadah, Muti’ah Nurul (Indonesian Journal of Pharmacy, 2022)
Mycobacterium smegmatis and Mycobacterium avium offer an advantage in examining tuberculosis-like effects and host immune defense. Therefore, the study aims to examine the effect of ursolic acid (UA) on the host immune system by analyzing cytokines concentration, such as TNF-α, IL-6, IL-1β, and nitrite oxide produced by murine macrophages infected with Mycobacterium smegmatis and Mycobacterium avium. Femurs of female C57BL/6 mice aged 6–8 weeks were used to culture the Bone marrow-derived macrophages (BMDM). On day 10, BMDM was infected with Mycobacterium smegmatis and Mycobacterium avium using a multiplicity of infection (MOI) amounting to 8:1, then TNF-α, IL-6, and IL-1β were analyzed using ELISA and nitrite oxide with Griess reagent. The results showed that UA decreased the production of three respective pro-inflammatory cytokines used in the study, both in BMDM infected by Mycobacterium smegmatis and Mycobacterium avium. For TNF-α, the reduction was nearly 65%-90% compared to the control. The decrease in the production of IL-6 occurred from 2700 pg/ml to 750 pg/ml for BMDM infected with Mycobacterium smegmatis, while the reduction was more significant in those infected using Mycobacterium avium with approximately 150 pg/ml compared to the control. Moreover, UA reduced by over 90% of IL-1β and this result was in line with the reduction of nitrite. UA decreases the production of pro-inflammatory cytokines such as TNF-α, IL-6, IL-1β, and nitrite. This result is preliminary but supports further study on the role of UA in immune defense from pathogenic and non-pathogenic mycobacterial infections.